2003
DOI: 10.1002/eji.200324223
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antigen‐specific T cells by cytokine flow cytometry: the use of whole blood may underestimate frequencies

Abstract: Antigen-specific T cells may be detected and enumerated by short-term ex vivo antigenspecific stimulation followed by cytokine flow cytometry. Most frequently, intracellular IFN-+ is used to identify T cells specific for cytomegalovirus (CMV), Epstein-Barr virus or HIV. Some researchers use whole blood, others peripheral blood mononuclear cells (PBMC) in this assay; however, the performance of the two systems has never been directly compared. Blood was drawn from previously characterized healthy CMV-positive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…However, our results are similar to those of Dunn et al, who similarly stimulated whole blood with CMV peptide pool and lysate (2). It is possible that use of whole blood may underestimate the frequency of CMV specific T cells as recently reported by Hoffmeister et al (27), although others have not observed significant quantitative differences in CMV-responses using these two types of specimens (28). The frequencies of CD8 + T cell IFNγ responses may also be lower in the present study due to the stringency in the cutoffs used.…”
Section: Discussionsupporting
confidence: 92%
“…However, our results are similar to those of Dunn et al, who similarly stimulated whole blood with CMV peptide pool and lysate (2). It is possible that use of whole blood may underestimate the frequency of CMV specific T cells as recently reported by Hoffmeister et al (27), although others have not observed significant quantitative differences in CMV-responses using these two types of specimens (28). The frequencies of CD8 + T cell IFNγ responses may also be lower in the present study due to the stringency in the cutoffs used.…”
Section: Discussionsupporting
confidence: 92%
“…Undiluted whole blood consistently yielded higher T cell frequencies than purified PBMCs [42]. However, a more recent study [26] also using similar stimuli and the same T cell readout (intracellular IFN-g staining) reached the opposite conclusion: responses were consistently higher in PBMCs than in whole blood, occurred at lower concentrations of stimulant and were sometimes detected only on PBMCs [26]. In conclusion, further studies are needed to settle the question of the sensitivity of whole blood versus PBMC assays, and how red blood cell lysis affects T cell recovery and function.…”
Section: Use Of Whole Blood Versus Pbmcsmentioning
confidence: 90%
“…However, when whole blood assays were performed in parallel, lithium heparin yielded slightly higher CMV-specific responses [26]. Hence, we recommend using heparin as anticoagulant for T cell assays (level of evidence: C).…”
Section: Anti-coagulantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surprisingly high concentration of IFN-␥ secreted into the extracellular medium in the subgroup of monoclonal TCRV␤13.1 ϩ /CD4 ϩ T-LGL patients in response to a single hCMV peptide complementary to the HLA-DRB1*0701 allele is particularly enlightening; this is particularly true if we consider that the observed response could represent only part of the response actually occurring in vivo because antigen presentation developed in vitro by PB cells could be considerably less efficient as it is limited to circulating cells (dendritic cells and B lymphocytes) that are considered to be precursors of professional antigen-presenting cells 44 and because of the potential interference of plasma proteins with both antigen uptake and HLA loading. 45 Immunologic T-cell responses against viruses and other antigens are typically associated with clonal selection of T cells with restricted antigen specificities. 46 This is particularly evident among CD8 ϩ cytotoxic/ effector T cells 46 ; in turn, CD4 ϩ T cells typically show a broader recognition of peptide epitopes probably the result of the existence of less stringent anchor positions in HLA class II vs HLA class I molecules.…”
Section: Discussionmentioning
confidence: 99%